Answer:
Jon lost a total of 3 kilograms in these 3 months.
Step-by-step explanation:
Weight that Jon gained in December = 2.2 kilograms
Weight that Jon lost in January = 1.5 kilograms
Weight that Jon lost in February = 3.7 kilograms
Overall Change in his weight = Total Weight he gained - Total weight he Lost
Total weight he gained is 2.2 kilograms as he only gained weight in December. Total weight he lost will be sum of weights he lost in January and February.
So, total weight Jon lost = 1.5 + 3.7 = 5.2 kilograms
Thus,
Total change in Jon's Weight = 2.2 - 5.2 = -3.0 kilograms
This shows that Jon lost a total of 3 kilograms in these 3 months.
Conclusion:
The statement that best describe the total change in his weight is: Jon lost a total of 3 kilograms in these 3 months
-4.5 or -4.3 i’m not really sure i’m just estimating
Answer:
Value of expression 1 = 3
Value of expression 2 = 42
Value of expression 3 = 15
Value of expression 4 = 2
Step-by-step explanation:
Expression 1 : the sum of m and 3 divided by the difference of m minus 3
Expression 1![: \frac{m+3}{m-3}](https://tex.z-dn.net/?f=%3A%20%5Cfrac%7Bm%2B3%7D%7Bm-3%7D)
Substitute m = 6
So, value of expression 1=![\frac{6+3}{6-3}=3](https://tex.z-dn.net/?f=%5Cfrac%7B6%2B3%7D%7B6-3%7D%3D3)
Expression 2 : the sum of 3 times m and 4 times m
Expression 2: 3m+4m
Substitute m = 6
So, value of expression 2=3m+4m=3(6)+4(6)=42
Expression 3 : the difference of the product of 3 and m minus the quotient of m divided by 2
Expression 3:![3m-\frac{m}{2}](https://tex.z-dn.net/?f=3m-%5Cfrac%7Bm%7D%7B2%7D)
Substitute m = 6
So, value of expression 2= ![3m-\frac{m}{2}=3(6)-\frac{6}{2}=15](https://tex.z-dn.net/?f=3m-%5Cfrac%7Bm%7D%7B2%7D%3D3%286%29-%5Cfrac%7B6%7D%7B2%7D%3D15)
Expression 4 :the quotient of 6 divided by the difference of m minus 3
Expression 4:![\frac{6}{m-3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7Bm-3%7D)
Substitute m = 6
So, value of expression 4=![\frac{6}{m-3}=\frac{6}{6-3}=2](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7Bm-3%7D%3D%5Cfrac%7B6%7D%7B6-3%7D%3D2)
I think it’s D but I am not sure
Answer:
NO
Step-by-step explanation:
The rule for Isosceles Triangle is that two of the sides (leg) must be congruent (have the same meaurement), while the base can be larger or smaller.
~